The Big Audition - Reddy, Swapna; Binny (Binny Talib) (New York : Random House, 2022)
In Millie's latest adventure, her favourite TV show, Ballet Beat, is coming to town! One lucky person will get the chance to appear on the show, but is Millie brave enough to audition? All she needs is a little encouragement from her friends, the Ballet Bunnies. With a Ballet Bunny on your side, fun and laughter are never far away.
Primary.
Keywords: Ballet -- Juvenile fiction; Rabbits -- Juvenile fiction; Screen tests -- Juvenile fiction; Animal fiction